BRICS sequential therapeutic regimen as first-Line treatment for PD-L1-negative metastatic non-small cell lung cancer patients harboring EGFR/ALK wild-type status: a retrospective study - Chen, Jianxin; Wang, Jian; Fang, Weiqiang; Wu, Yating; Li, Hang; Xu, Hui; Zhu, Yunyun; Cheng, Yanran; Yu, Zongyang; Peng, Yonghai (Frontiers in Immunology, 2025)
BackgroundPatients with PD-L1-negative, EGFR/ALK wild-type metastatic non-small cell lung cancer (NSCLC) exhibit limited responses to immune checkpoint inhibitors (ICIs). This study evaluates the BRICS regimen-a sequential approach combining stereotactic body radiotherapy (SBRT), probiotics, PD-1 inhibitors, and low-dose chemotherapy-to overcome immunotherapy resistance.MethodsThis retrospective study included 23 patients treated between 2018 to 2024. Eligibility criteria: confirmed PD-L1-negative NSCLC, no actionable mutations, and measurable lesions. The BRICS regimen comprised SBRT (24 Gy in 3 fractions) to a single lesion, oral probiotics (6 g/day), low-dose chemotherapy, and PD-1 inhibitors administered every 21 days for six cycles. Outcomes included objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety.ResultsMedian age was 62 years; 82.6% were male. ORR and DCR were both 95.7%. Median PFS was 16 months (95% CI: 9.11-22.89), and median OS was 32.7 months (95% CI: 11.53-53.87). In subgroup analysis based on prior treatment status, median PFS and OS were numerically longer in treatment-naïve patients compared to previously treated patients (mPFS: 20.0 vs. 13.6 months; mOS: 48.0 vs. 18.0 months), though without statistical significance (P > 0.05). Poor ECOG performance status predicted poorer PFS (HR=9.908, p=0.013) and OS (HR=26.406, p=0.008). Adverse events were predominantly grade 1 to 2 (fatigue:13.2%, rash:8.7%), with no grade ≥3 toxicities.ConclusionsThe BRICS regimen demonstrated promising efficacy and safety in PD-L1-negative NSCLC, potentially overcoming resistance through multimodal immunomodulation. clinical benefit was observed regardless of treatment line, with a trend toward improved outcomes when administered as first-line therapy. Prospective trials are warranted to validate these findings and explore mechanisms underlying radiotherapy–microbiome–chemotherapy synergy.